Species delineation of Malaysian mangrove fireflies (Coleoptera: Lampyridae) using DNA barcodes - Jusoh, Wan Faridah Akmal; Hashim, Nor Rasidah; Saaksjarvi, Ilari Eerikki; Adam, Nur Azura; Wahlberg, Niklas (BioOne, 2014)
Identification and revision of firefly species are largely based on morphological characteristics. Subsequently, female firefly specimens have been neglected in taxonomic inventories because morphological descriptions relied only on male firefly specimens. In light of successful DNA barcoding in many invertebrates, this study explored the potential of DNA barcoding to complement morphological identification of fireflies in Malaysia. Firefly specimens were collected from riparian forests (including mangroves) in Peninsular Malaysia and Sarawak. Specimens were morphologically examined, and their DNA was extracted for molecular analysis. The morphological data of the male specimens was found to be congruent with molecular data, i.e., both indicated 12 species. However, inclusion of females and larvae in the DNA analysis increased the species count to 14 species. We also found distinct geographically structured variations in the DNA barcodes of two species: Pteroptyx tener Olivier and Pteroptyx bearni Olivier. The study indicates that firefly species delimitation using traditional taxonomic knowledge and new technology like DNA barcoding are compatible, therefore increasing the reliability of species identification.